Isolation of Flavonoids and Triterpenoids from the Fruits of Alphitonia Neocaledonica and Evaluation of their Anti‐oxidant, Anti‐tyrosinase and Cytotoxic Activities. Issue 2 (16th December 2014) - Muhammad, Dima; Hubert, Jane; Lalun, Nathalie; Renault, Jean‐Hugues; Bobichon, Hélène; Nour, Mohammed; Voutquenne‐Nazabadioko, Laurence
Abstract Introduction Alphitonia neocaledonica (Rhamnaceae) is an endemic tree of New Caledonia. Although three flavonoids have been identified in the leaves, the secondary metabolite profile of the fruits has never been investigated. Objective Phytochemical investigation of A. neocaledonica fruits and evaluation of their anti‐oxidant, anti‐tyrosinase and cytotoxic activities. Methods A hydromethanolic extract was fractionated by liquid–liquid extraction to obtain ethyl acetate and n‐butanolic fractions. The ethyl‐acetate‐soluble part was purified by silica‐gel column chromatography and high‐performance liquid chromatography (HPLC). The n‐butanol‐soluble part was fractionated by centrifugal partition extraction (CPE) and the collected fractions were further purified by centrifugal partition chromatography (CPC) and HPLC. The chemical structures of the purified compounds were identified by nuclear magnetic resonance and mass spectrometry. Results Three triterpenoids and one flavonoid were isolated from the ethyl‐acetate‐soluble part. Fractions enriched in triterpenoids, flavonoids and catechin derivatives were obtained from the n‐butanol‐soluble part. Gallocatechin and flavonoids were obtained as pure compounds by further CPC and HPLC purification. The n‐butanolic‐soluble part showed anti‐oxidant and anti‐tyrosinase activities due to the presence of tannins and gallocatechin. The triterpenoid alphitolic acid showed a moderate cytotoxic activity against KB cell line (median inhibition concentration = 8.5 μM). Conclusions Nine known compounds including three triterpenes, five flavonoids and (+) gallocatechin, as well as a new 3‐O‐(6‐E‐feruloyl)‐β‐D‐glucopyranosyl‐(1 → 2)‐[β‐D‐xylopyranosyl‐(1 → 2)‐]α‐L‐rhamnopyranosyl‐quercetin, were isolated from A. neocaledonia fruits. The hydromethanolic extract possesses a potential cytotoxic activity due to the presence of triterpenes, and it can also be valuable as a cosmetic ingredient for its anti‐oxidant and anti‐tyrosinase activities. Copyright © 2014 John Wiley & Sons, Ltd.